DECARBONIZATION AS A FACTOR FOR IMPROVING THE QUALITY OF MANAGEMENT OF INDUSTRIAL ENTERPRISES - STANKOVSKA, Iryna; SMAGA, Lubomyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The topic of the article is “Decarbonization as a factor for improving the quality of management of industrial enterprises”.The purpose of the study is the issue of implementing and evaluating decarbonization as a component of ensuring the quality of enterprise management, assessing the energy and carbon maturity of the enterprise. To achieve the set goal, the methods of analysis and synthesis, theoretical generalization, comparison, and modeling were used. The paper substantiates the feasibility of applying decarbonization at the enterprise; identifies the areas of management of decarbonization processes; investigates the impact of decarbonization on the quality of production processes and areas of enterprise management; forms an energy maturity matrix for the implementation and management of the decarbonization strategy. Five levels of energy and carbon maturity and parameters for controlling the implementation of each level are identified and characterized.The scientific novelty lies in the application of decarbonization as a factor characterizing the quality of management of an industrial enterprise and the formation of a matrix of energy and carbon maturity of the enterprise.The identified parameters of control of the energy and carbon maturity of the enterprise have gained practical significance, which makes it possible to assess the state of the organization in the studied period. The identification of such criteria, in turn, will serve as a guide and help develop a plan that must be implemented in order to become a more mature enterprise in the direction of decarbonization.According to the results of the study, it is substantiated that the implementation of decarbonization indicates the quality of enterprise management; it is proven that the implementation of decarbonization increases the overall maturity in the management of production processes, operational efficiency and cost optimization, which is consistent with the goals of sustainable development and environmental, social and governance criteria (ESG); a model for assessing energy and carbon readiness is proposed, providing enterprises with a comprehensive tool for assessing the current state and identifying areas for further improvement.
Keywords: decarbonization; sustainable development; quality of management; industrial enterprises; competitiveness